Effectiveness of Dapagliflozin in Reducing Incidence of Worsening Heart Failure Events among patients with Reduced Ejection Fraction - Mohammad Asif, Talha Laique (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Sodium–glucose co-transporter 2 (SGLT2) inhibitors are the groups of oral hypoglycemics that decreases the worse events among cardiac patients of chronic heart failure. Aim: To assess the effectiveness of Dapagliflozin in reducing the incidence of worsening heart failure events among chronic heart failure patients. Study design: Randomized controlled trial. Methodology: This study enrolled 480 cardiac patients with mildly reduced ejection fraction. This study was held at Punjab Institute of Cardiology. All patients received dapagliflozin 10mg once daily or matching placebo, in addition to usual therapy for four weeks. The data was entered and analyzed in SPSS 25. Independent sample t-test was used to compare the mean age and body mass index between two groups. Chi square test was used to compare gender and hypertension with primary composite. Results: There were 138(57.5%) males in Dapagliflozin group and 131(54.6%) males in placebo group. Dapagliflozin demonstrated significant benefits compared to placebo, as evidenced by lower rates of the primary composite outcome (15.8% vs. 23.3%, p = 0.038), hospitalization for heart failure or an urgent visit (10.4% vs. 20.0%, p = 0.003). Practical Implication: Chronic heart failure with mildly reduced ejection fraction is a major problem in modern era. Present study will highlight the effect of oral hypoglycemic, dapagliflozin, in reducing worse cardiovascular events among chronic heart failure patients. As there is a lack of local literature review on this health issue so this study added information to existing literature and add new dimensions in its treatment. Conclusion: It was concluded that dapagliflozin reduced worsening of cardiac events among heart failure patients with mildly reduced ejection fraction thus this drug is effective treatment option among cardiac failure patients in reducing hospitalization. Keywords: Heart Failure, Reduced Ejection Fraction, Effectiveness, Urgent Visits and Hospitalization.